From the fjords to the Nile : essays in honour of Richard Holton Pierce on his 80th birthday - Steiner, Pål,; Tsakos, Alexandros,; Seland, Eivind Heldaas,; Pierce, Richard Holton, (Archaeopress Publishing Ltd, 2018)
'From the Fjords to the Nile' brings together essays by students and colleagues of Richard Holton Pierce, presented on the occasion of his 80th birthday. It covers topics on the ancient world and the Near East. Pierce is Professor Emeritus of Egyptology at the University of Bergen. Starting out as an expert in Egyptian languages, and of law in Greco-Roman Egypt, his professional interest has spanned from ancient Nubia and Coptic Egypt, to digital humanities and game theory. His contributions as scholar, teacher, supervisor and informal advisor to Norwegian studies in Egyptology, classics, archaeology, history, religion, and linguistics through more than five decades can hardly be overstated.